Voices from the Radio Operator’s House: A partial translation of Steinunn G. Helgadóttir’s Raddir úr húsi loftskeytamannsins and accompanying methodological analysis - Kyzer, Larissa Darlaine, 1984- (2017)
This thesis is a translated excerpt of the short story cycle Raddir úr húsi loftskeytamannsins, accompanied by both a brief literary analysis of the text as well an analysis of my own translation process. The thesis is divided into four chapters. In the first, I introduce the text, examine it in terms of its genre—a short story cycle—and its primary stylistic features, discuss its critical reception in Iceland, and identify the scope of my excerpted English translation of the text. Chapter two delves into translation theory, with particular reference to Hans Vermeer’s skopos theory and Katharina Reiss’ text types. It also discusses the ‘creative’ methods of translation and identifies the skopos of the present translation. In chapter three, I look at the major challenges I encountered while translating Raddir úr húsi loftskeytamannsins and how I used the previously discussed creative strategies to address these. Chapter four is a brief conclusion. My translation excerpt, “Voices from the Radio Operator’s house,” comprises the first nine stories of the source text, or roughly one third of the book. Þessi ritgerð er þýðing á hluta smásögusafnsins Raddir úr húsi loftskeytamannsins, ásamt stuttri bókmenntagreiningu og greiningu þýðingarferlisins. Ritgerðin skiptist í fjóra kafla. Í þeim fyrsta kynni ég textann, rýni í hann m.t.t. bókmenntagreinarinnar – þ.e. sagnasveiga – og helstu stíleinkenna, ræði um hvernig bókinni var tekið á Íslandi og greini umfang þýðingar minnar á hluta textans yfir á ensku. Í öðrum kafla ræði ég þýðingarfræði og sérstaklega kenningu Hans Vermeer um skopos og textagerðir Katharinu Reiss. Ég kem einnig inn á aðferðir þar sem þýðandi leyfir sér að vera „skapandi“ og greini skopos þýðingarinnar sem fyrir liggur. Í þriðja kafla fjalla ég um stærstu áskoranirnar sem ég þurfti að takast á við þegar ég þýddi Raddir úr húsi loftskeytamannsins og útskýri hvernig þær skapandi aðferðir, sem ég nefndi í þriðja kafla, komu að gagni í þeim efnum. Í fjórða kafla fjalla ég stuttlega um helstu niðurstöður. ...